RESPON PERTUMBUHAN ANGGREK TEBU (Grammatophyllum speciosum BLUME) SECARA IN VITRO TERHADAP PEMBERIAN BENZYL AMINO PURIN, KINETIN, NAFTALENA ACETIC ACID DAN EKSTRAK PISANG AMBON DALAM MEDIA DASAR SETENGAH MURASHIGE AND SKOOG - Ellok Dwi Sulichantini; Eliyani Eliyani; Alvera Prihatini Dewinazari; Susylowati Susylowati; Agusty Saputra (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Kalimantan whose existence is increasingly extinct so it needs to be preserved by in vitro propagation. This study aims to determine the effect of a combination of the growth regulators, Benzyl Amino Purin (BAP), Kinetin, Naphthalene Acetic Acid (NAA) and banana extract on the growth of sugar cane orchids in vitro. The basic media used were Half Murashige and Skoog (1/2 MS), on the base media were added 30 g.L-1 sugar, 8 g.L-1 seaweed commercial powder,  plus BAP 3 ppm, Kinetin 3 ppm, NAA 0.5 ppm, and ambon banana extract 100 g.L-1, the acidity (pH) of the media is adjusted to around 5.8. The research design used was a Completely Randomized Design (CRD), each treatment was repeated six times. Data were analyzed using variance analysis and continued with DMRT (Duncan Multiple Range Test) tests with a level of 5%.            The results showed that the half media Murashige and Skoog was good for the propagation of sugarcane orchids.  The addition of BAP growth regulators, Kinetin, NAA, and banana extracts showed a good response to growth culture. The addition of BAP 3 ppm + NAA 0.5 ppm showed the best results for the height increased, leaf number increased, leaf length increased, leaf width increased, and the number of shots increased. The addition of Ambon banana extract to media containing growth regulators tended to decrease the growth response, seen in the parameters of plant height increased, leaf number increased, leaf length increased, leaf width increased, the number of shoots increased, the number of roots increased and in root length increased.